The clinical profile of high-risk mentally disordered offenders - Yiend, J; Freestone, M; Vazquez-Montes, M; Holland, J; Burns, T (2013)
Purpose: High-risk mentally disordered offenders present a diverse array of clinical characteristics. To contain and effectively treat this heterogeneous population requires a full understanding of the group's clinical profile. This study aimed to identify and validate clusters of clinically coherent profiles within one high-risk mentally disordered population in the UK. Methods: Latent class analysis (a statistical technique to identify clustering of variance from a set of categorical variables) was applied to 174 cases using clinical diagnostic information to identify the most parsimonious model of best fit. Validity analyses were performed. Results: Three identified classes were a 'delinquent' group (n = 119) characterised by poor educational history, strong criminal careers and high recidivism risk; a 'primary psychopathy' group (n = 38) characterised by good educational profiles and homicide offences and an 'expressive psychopathy' group (n = 17) presenting the lowest risk and characterised by more special educational needs and sexual offences. Conclusions: Individuals classed as high-risk mentally disordered offenders can be loosely segregated into three discrete subtypes: 'delinquent', 'psychopathic' or 'expressive psychopathic', respectively. These groups represent different levels of risk to society and reflect differing treatment needs. © 2013 Springer-Verlag Berlin Heidelberg.